Penggunaan kecerdasan buatan sebagai indikator untuk mengklasifikasikan efektivitas lempar lembing siswa dalam atletik Berdasarkan beberapa keterampilan fisik dan motorik serta ukuran tubuh - Ahmed Hamza Hassan Jaber; Mahmoud Adnan Mahmoud Kaid (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. To determine the authenticity of the sample based on the physical and athletic skills and body measurements of some students, with the goal of classifying them into homogeneous groups and to group pupils according to their body measurements and certain athletic and physical attributes. Materials and methods. The researchers described the concept of his current research in a comprehensive manner within the theoretical framework. Methodologically, the opted for descriptive research and correlational methods because of his compatibility and the problem he wanted to address. The research team was comprised of third year students (115 students) from the faculty of Sport and Exercise Sciences at the University of Babylon during the academic year 2022/23. The researcher described the procedures used to accomplish his research and achieve his goals Results. The table indicates that the explosive power of the legs x the fourth cell had the highest coefficient value in the negative direction, reaching -1.117, and the explosive power of the arms x the ninth cell had the highest coefficient value, reaching 0.886 in the positive direction. The other coefficient values varied between these values Conclusions. Using statistical metrics associated with normal distribution, these estimates suggest that the sample components are approximately distributed across all of the study variables, this enables the researchers to create models for categorization purposes and the researchers were able to create models of how various variables influence class: (weight, arm length, hand length, chest width, upper arm circumference, leg power, arm power, balance and coordination).